2012
DOI: 10.3402/tellusa.v64i0.18486
|View full text |Cite
|
Sign up to set email alerts
|

HOAPS precipitation validation with ship-borne rain gauge measurements over the Baltic Sea

Abstract: A B S T R A C T Global ocean precipitation is an important part of the water cycle in the climate system. A number of efforts have been undertaken to acquire reliable estimates of precipitation over the oceans based on remote sensing and reanalysis modelling. However, validation of these data is still a challenging task, mainly due to a lack of suitable in situ measurements of precipitation over the oceans. In this study, validation of the satellite-based Hamburg Ocean Atmosphere Parameters and fluxes from Sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…As a useful measure for these collocation boundaries, spatial decorrelation lengths can be used that denote the distance at which the spatial correlation of a signal with respect to a location decreases to1/ e . Bumke et al () found decorrelation lengths of 46–68 km for frontal and stratiform precipitation and 18–46 km for convective precipitation. Based on these decorrelation lengths, Bumke et al () chose ±25 km and±30 min for collocating precipitation derived from the same optical disdrometer ODM470 on board RV Alkor with HOAPS over the Baltic Sea for the period 1995–1997.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a useful measure for these collocation boundaries, spatial decorrelation lengths can be used that denote the distance at which the spatial correlation of a signal with respect to a location decreases to1/ e . Bumke et al () found decorrelation lengths of 46–68 km for frontal and stratiform precipitation and 18–46 km for convective precipitation. Based on these decorrelation lengths, Bumke et al () chose ±25 km and±30 min for collocating precipitation derived from the same optical disdrometer ODM470 on board RV Alkor with HOAPS over the Baltic Sea for the period 1995–1997.…”
Section: Methodsmentioning
confidence: 99%
“…Bumke et al () found decorrelation lengths of 46–68 km for frontal and stratiform precipitation and 18–46 km for convective precipitation. Based on these decorrelation lengths, Bumke et al () chose ±25 km and±30 min for collocating precipitation derived from the same optical disdrometer ODM470 on board RV Alkor with HOAPS over the Baltic Sea for the period 1995–1997. For snowfall over the Norwegian Sea, Klepp et al () successfully applied more generous collocation boundaries of ±55 km and±45 min with an accuracy of 0.99.…”
Section: Methodsmentioning
confidence: 99%
“…However, satellite-based precipitation is not measured directly, but derived from radiance measurements. Validation of satellite-based data with in situ measurements from rain gauges on ships within the Baltic Sea shows precipitation is underestimated by remote sensing, because the detectability of small-scale precipitation typical of convective weather conditions is too low, although the detectability in cases of prevailing stratiform clouds fits well (Bumke et al 2012). A first estimation for mean monthly, seasonal and annual precipitation totals was determined from the Scanning Multispectral Microwave Radiometer (SMMR) data on the Nimbus-7 satellite for the period 1978-1987 by retrieving the relationship of 37 GHz horizontal channel brightness temperatures to rain-rates (mm h −1 ) from the calibration of the SMMR data by contemporaneous data from the Camborne radar station (Cornwall) of the UK Meteorological Office and published by Barrett et al (1991 The HOAPS data show May as the driest month with average precipitation amounts of less than 25 mm in an extended area east and north of the British Islands.…”
Section: 542mentioning
confidence: 99%
“…In this study precipitation data from 1995-1997, gained over the Atlantic Ocean and the tropical Pacific Ocean, and2005-2008, gained mainly over the Atlantic Ocean, together yield a point-to-area collocation against the satellite-derived climatology HOAPS and ERA-Interim reanalysis data. As in a similar validation study over the Baltic Sea (Bumke et al, 2012), the nearest neighbour approach was chosen for collocation. Therefore, it must be ensured that both observations are related to each other, which can be determined by an appropriate decorrelation length.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it must be ensured that both observations are related to each other, which can be determined by an appropriate decorrelation length. Decorrelation lengths had been derived from in situ precipitation data over the Baltic Sea: 17 km based on disdrometer 8 min time series (Bumke et al, 2012), 25 km for convective precipitation and 46-68 km for stratiform/frontal precipitation, based on 8 min time series of SRG measurements (Clemens and Bumke, 2002) on board merchant ships. Using 46 km as the decorrelation length for stratiform/frontal precipitation, these three numbers give an average decorrelation length of about 30 km which agrees well with a study of Puca et al (2014).…”
Section: Methodsmentioning
confidence: 99%